Health Education and Socialization about Physical Activities/Sports in RW 06 Tanjung Merpati Village Kembayan District Sanggau Regency - Manik, Novelita Br; Ardayani, Tri; Hotmaida, Linda; Sitorus, Neti; Yogisutanti, Gurdani; Fuadah, Fahmi (CV Media Inti Teknologi, 2025)
This activity aims to plan community service activities to solve problems obtained based on situation analysis, prioritizing problems by providing health education to the community to always maintain health. The method used consists of preparation, implementation, and closing. Preparation was carried out with various activities including field surveys, problem identification, approaches to the community, situation analysis, and proposal preparation carried out in August 2024. Implementation was carried out in September 2024 with counseling preparation activities and counseling activities through the delivery of material on Physical Activity/exercise. Closing activities are carried out by compiling reports. Implementing community service activities on Health Education Education on physical activity/exercise in the RW 06 area of Tanjung Merpati Village, Kembayan District, Sanggau Regency can be carried out well, smoothly and conducive. The results showed that community knowledge about the meaning, causes, symptoms, prevention, treatment, and impact of physical activity/exercise had increased. This community service activity is expected to bring real benefits to the Tanjung Merpati village community and become an inspiration for similar efforts in various regions.